(untitled) (Interdisciplinary Research in Education, 2019)
This study is followed the descriptive and analytical research design under quantitative inquiry approach as its aims to analyze and compare institutional and non-institutional direct private cost. Furthermore, it tries to find out the size of institutional and non-institutional direct private cost at bachelor level of Nepal. For these purposes, researcher has selected a community based college from Kathmandu valley purposively using simple random sampling. The findings of the study reveal that per student average college related institutional unit cost was Rs 24730. 57, university related institutional cost was Rs 5982.23 and total annual institutional unit cost was Rs 30712.80. Likewise, it was found that a student has expensed Rs 46411.63 as non-institutional direct private cost in a year. Total annual average direct private cost of education (institutional plus non-institutional) was Rs 77124.43 at bachelor level of community based college in the capital city of Nepal.